TRAIL-induced apoptosis: from analysis of the death-inducing signalling complex (DISC) to clinical applicability - Walczak, Henning (Henry Stewart Talks, 2007)
poptosis induction by the TNF-related apoptosis-inducing ligand (TRAIL), Apoptosis-inducing TNF super-family ligands and receptors, Formation of the deathinducing signalling complex (DISC), Caspase-8 versus caspase-10, Synergy of TRAIL with chemotherapeutics, Tumour specificity of TRAIL-induced apoptosis, Regulation of sensitivity versus resistance towards TRAIL-induced apoptosis